2007
DOI: 10.3200/gntp.167.4.365-382
|View full text |Cite
|
Sign up to set email alerts
|

Reactive and Proactive Aggression: Stability of Constructs and Relations to Correlates

Abstract: The authors examined short-term temporal stability of reactive and proactive aggression, as well as short-term consistency of differential relations of reactive versus proactive aggression to 4 correlates. The authors used parent, teacher, peer, and self-report measures twice across 1 year to assess reactive aggression, proactive aggression, hyperactivity, social skills, anger expression, and depressive symptoms of 2nd-grade boys and girls (N = 57). Both subtypes of aggression remained stable across the year, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 34 publications
6
47
0
4
Order By: Relevance
“…Previous research has revealed a significant relation between low social cognitive skills and reactive aggression (Day et al 1992;McAuliffe et al 2007). What seems to be particularly characteristic of reactively aggressive children is their tendency to suspect hostile intentions in others when a social situation leads to a negative outcome for themselves, even when the other person's intention is ambiguous (Crick and Dodge 1996;Dodge and Coie 1987;Schwartz et al 1998).…”
Section: Theory Of Mind and Reactive Aggressionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research has revealed a significant relation between low social cognitive skills and reactive aggression (Day et al 1992;McAuliffe et al 2007). What seems to be particularly characteristic of reactively aggressive children is their tendency to suspect hostile intentions in others when a social situation leads to a negative outcome for themselves, even when the other person's intention is ambiguous (Crick and Dodge 1996;Dodge and Coie 1987;Schwartz et al 1998).…”
Section: Theory Of Mind and Reactive Aggressionmentioning
confidence: 98%
“…As an organized and planned behavior, proactive aggression is related to the anticipation of a positive outcome of the aggressive behavior (Dodge et al 1997). Although studies usually report a high correlation between reactive and proactive aggression (mean r=0.68; Card and Little 2006), factor analyses and meta-analyses provide clear evidence for the validity of the distinction between the two functions of aggression (Card and Little 2006;Crick and Dodge 1996;McAuliffe et al 2007;Poulin and Boivin 2000;Vitaro et al 1998). As will be discussed in more detail below, evidence also suggests that these two functions of aggressive behavior are differentially related to social cognitive skills, particularly with respect to the decoding of social stimuli (Crick and Dodge 1996;Dodge et al 1997;Dodge and Coie 1987;Hubbard et al 2001;Schippel et al 2003).…”
mentioning
confidence: 99%
“…According to research results, reactive aggression is associated with internal symptoms such as negative emotions, anxiety and depression (Card and Little, 2006;Raine et al, 2006;Fite et al, 2009;Vitaro et al, 2002). It was stated that reactive aggression in children and adolescents has a positive relationship with depressive symptoms (McAuliffe et al, 2006) and anxiety (Marsee et al, 2008). Similarly, reported that depression of reactive aggressive children is higher than proactive aggressive children.…”
Section: Introductionmentioning
confidence: 97%
“…Treatment effectiveness has been directly related to the use of subtype-specific treatment protocol with aggressive children and adolescents (McAdams, 2002). For example, McAuliffe, Hubbard, Rubin, Morrow, & Dearing (2007) suggested that interventions aim at reactive aggression would emphasize anger management, peer relations and social skills training, hostile attributional bias reduction, social problem solving and reductions in internalizing symptoms. Conversely, treatment for proactive aggression would stress development of empathy, negative consequences of aggressive behavior and importance of social goals.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Reactive and proactive aggression are also differentiated by parental attitudes. McAuliffe, Hubbard, Rubin, Morrow and Dearing (2007) suggests that reactive aggression grows out of earlier physical abuse and harsh parenting, whereas proactive aggression results from earlier exposure to aggressive models.…”
mentioning
confidence: 99%